Altered Spontaneous Brain Activity in Betel Quid Dependence: A Resting-state Functional Magnetic Resonance Imaging Study. Issue 5 (February 2016) - Liu, Tao; Li, Jian-jun; Zhao, Zhong-yan; Yang, Guo-shuai; Pan, Meng-jie; Li, Chang-qing; Pan, Su-yue; Chen, Feng
Abstract : Abstract: It has been suggested by the first voxel-based morphometry investigation that betel quid dependence (BQD) individuals are presented with brain structural changes in previous reports, and there may be a neurobiological basis for BQD individuals related to an increased risk of executive dysfunction and disinhibition, subjected to the reward system, cognitive system, and emotion system. However, the effects of BQD on neural activity remain largely unknown. Individuals with impaired cognitive control of behavior often reveal altered spontaneous cerebral activity in resting-state functional magnetic resonance imaging and those changes are usually earlier than structural alteration. Here, we examined BQD individuals (n = 33) and age-, sex-, and education-matched healthy control participants (n = 32) in an resting-state functional magnetic resonance imaging study to observe brain function alterations associated with the severity of BQD. Amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) values were both evaluated to stand for spontaneous cerebral activity. Gray matter volumes of these participants were also calculated for covariate. In comparison with healthy controls, BQD individuals demonstrated dramatically decreased ALFF and ReHo values in the prefrontal gurus along with left fusiform, and increased ALFF and ReHo values in the primary motor cortex area, temporal lobe as well as some regions of occipital lobe. The betel quid dependence scores (BQDS) were negatively related to decreased activity in the right anterior cingulate. The abnormal spontaneous cerebral activity revealed by ALFF and ReHo calculation excluding the structural differences in patients with BQD may help us probe into the neurological pathophysiology underlying BQD-related executive dysfunction and disinhibition. Diminished spontaneous brain activity in the right anterior cingulate cortex may, therefore, represent a biomarker of BQD individuals.